TLR4 agonist protects against Trypanosoma cruzi acute lethal infection by decreasing cardiac parasite burdens. (12th July 2020) - Villanueva‐Lizama, Liliana E.; Cruz‐Chan, Julio V.; Versteeg, Leroy; Teh‐Poot, Christian F.; Hoffman, Kristyn; Kendricks, April; Keegan, Brian; Pollet, Jeroen; Gusovsky, Fabian; Hotez, Peter J.; Bottazzi, Maria Elena; Jones, Kathryn M.
Abstract: E6020 is a synthetic agonist of Toll‐like receptor‐4 (TLR4). The purpose of this study was to evaluate the effect of different doses of E6020‐SE on Trypanosoma cruzi ‐specific immune responses and its ability to confer protection against acute lethal infection in mice. Forty female BALB/c were infected with 500 trypomastigotes of T cruzi H1 strain, divided into four groups (n = 10) and treated at 7‐ and 14‐day post‐infection (dpi) with different doses of E6020‐SE or PBS (control). Survival was followed for 51 days, mice were euthanized and hearts were collected to evaluate parasite burden, inflammation and fibrosis. We found significantly higher survival and lower parasite burdens in mice injected with E6020‐SE at all doses compared to the control group. However, E6020‐SE treatment did not significantly reduce cardiac inflammation or fibrosis. On the other hand, E6020‐SE modulated Th1 and Th2 cytokines, decreasing IFN‐γ and IL‐4 in a dose‐dependent manner after stimulation with parasite antigens. We conclude that E6020‐SE alone increased survival by decreasing cardiac parasite burdens in BALB/c mice acutely infected with T cruzi but failed to prevent cardiac damage. Our results suggest that for optimal protection, a vaccine antigen is necessary to balance and orient a protective immune response.